Forest and firewood in the kingdom of Valencia in the medieval centuries (XIII-XV) (Estudios de Historia de España, 2020)
We carry out an edaphological and historical analysis of the forest and its predominant species in the old Kingdom of Valencia between the XIII-XV centuries. It’s operation was carefully regulated by the royal, stately and municipal authorities, to avoid abusive felling, the excesses of cattle, loggers and coal miners. We place special emphasis on the use of firewood, its transactions or the footprints it has left in urban toponymy.
Keywords: Medium vegetable; forest; firewood; Kingdom of Valencia; economy